Teachers Language in English Foreign Language (EFL) Classroom of English Education Study Program in STAIN Parepare - Mujahidah, Mujahidah (IAIN Sultan Amai Gorontalo, 2015)
A teacher language is important for both the organization of the classroom and the processes of second and foreign language acquisition. The use of target language and native language is still discussion of English education experts now. This research aims to analyze and to describe teacher language relates to the use of native language and target language in teaching in EFL classroom and to find out the studentsâ perception toward teacher language in EFL classroom. The result of the research is expected to enrich theory of the use of native and target language in EFL classroom so that the theory can be used by teacher to refine the appropriate and effective use of native and target language in EFL classroom to improve studentsâ level of proficiency in English, especially in English Education Program in STAIN Parepare. The design of research is survey research. The research takes four English teachers (listening, speaking, reading, and writing teachers) as data resources. It uses observation and questionnaire in collecting data.Â In analyzing data, the researchers use statistic descriptive. The research findings show Listening teacher uses 57% target language and 43% native language. The portion is perceived good. Speaking teacher uses 57% target language and 43% native language. The portion is perceived good. Reading teacher uses 92% target language and 8% native language. The portion is perceived good. Writing teacher uses 29% target language and 71% native language. Target language portion is perceived fair but native language portion is perceived good.